In soil measurement of radiation dose caused by X‐ray computed tomography. Issue 3 (8th March 2021) - Lippold, Eva; Kleinau, Philip; Blaser, Sebastian R. G. A.; Schlüter, Steffen; Phalempin, Maxime; Vetterlein, Doris
Abstract: Radiation damage to plants through X‐ray exposure has been reported to impair root growth. The literature on the critical dose for growth impairment is inconclusive, partly as dose measurements in soil are scarce. Here we fill this gap and show that the dose in a typical single pot scan amounts to 1.2 Gy. In addition, we demonstrate the shortcomings of estimating the dose from scan settings using the RadPro Calculator and highlight the efficient reduction of X‐ray exposure by a lead shield.